Information and communications technologies and multimedia content as motivational factors for new generations of students - Marković Blagojević, Marija; Medić, Zorica; Cogoljević, Maja; Milićević, Raica (Serbian Journal of Management, 2021)
This paper deals with the theoretical analysis of the principles of efficient use of information and communications technologies (ICT) in teaching and learning, which can contribute to the advancement of the teaching process and motivation of students/pupils in the achieving the planned activities. Apart from the theoretical analysis, the results of empirical research are also presented in the paper. They tested and practically confirmed that there is a significant influence of the application of ICT and enriching the teaching material with multimedia content and also the effects in contemporary teaching of information technology. The primary intention of this paper is to point out the importance of the introduction of ICT to the teaching process with the aim of a significant improvement of students’/pupils’ learning through the increase of their motivation and efficiency in learning, and at the same time the improvement in the performance of the educational system.